2008
DOI: 10.3336/gm.43.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Fibonacci Diophantine triples

Abstract: Abstract. In this paper, we show that there are no three distinct positive integers a, b, c such that ab + 1, ac + 1, bc + 1 are all three Fibonacci numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
2
26
0
3
Order By: Relevance
“…Florian Luca és Szalay László [2] bebizonyították, hogy a Fibonacci sorozathoz nem adható meg diofantikus számhármas, azaz nincsenek olyan 0 < < < egészek, hogy + 1 = , + 1 = és + 1 = volna valamely x, y és z indexekre. Szintén az ő eredményük [3], hogy a Fibonacci-sorozat asszociáltjához, a Lucassorozathoz egyetlen ilyen hármas létezik: = 1 , = 2 és = 3 .…”
Section: Bevezetésunclassified
“…Florian Luca és Szalay László [2] bebizonyították, hogy a Fibonacci sorozathoz nem adható meg diofantikus számhármas, azaz nincsenek olyan 0 < < < egészek, hogy + 1 = , + 1 = és + 1 = volna valamely x, y és z indexekre. Szintén az ő eredményük [3], hogy a Fibonacci-sorozat asszociáltjához, a Lucassorozathoz egyetlen ilyen hármas létezik: = 1 , = 2 és = 3 .…”
Section: Bevezetésunclassified
“…According to Theorem 1, there should be only finitely many triples of distinct positive integers {a, b, c} such that ab + 1, ac + 1 and bc + 1 are either all three Fibonacci numbers or all three Lucas numbers. In [12], we showed that there is no such triple for the case of the Fibonacci sequence. In this paper, we deal with the same problem for the case of the Lucas sequence.…”
Section: Theoremmentioning
confidence: 99%
“…Proof. This is Lemma 6 in [12]. We point out that the particular cases λ = 1 and λ = 3 of Lemma 10 were used in [12].…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…(k, ) = (3, 2), (4, 3), (5, 3), (5,4), (6,5), (7,4), (7,5), (7,6), the previous argument provides the upper bounds …”
Section: Going Through the Eligible Pairsmentioning
confidence: 99%